Vaccine Inequity and Hesitancy: A Vicious Cycle Undermining the Fight Against the COVID-19 Pandemic - Gudina EK (Risk Management and Healthcare Policy, 2022)
Esayas Kebede Gudina,1 Zeleke Mekonnen,2 Daniel Yilma1 1Department of Internal Medicine, Jimma University Institute of Health, Jimma, Ethiopia; 2School of Medical Laboratory Sciences, Jimma University Institute of Health, Jimma, EthiopiaCorrespondence: Esayas Kebede Gudina, Department of Internal Medicine, Jimma University Institute of Health, P. O.Box 5058, Jimma, Ethiopia, Email esayas.gudina@ju.edu.etAbstract: The world has come a long way in the fight against the COVID-19 pandemic by averting the initially feared humanitarian crisis and by producing effective vaccines in a record time. Paradoxically, more new daily cases are being reported today than when there was not any effective vaccine around. The success against the pandemic so far is dented by inadequate vaccine supply in most low-income countries and widespread vaccine hesitancy. By the end of 2021, only half of WHO Member States have reached the target of immunizing 40% of their populations, while only less than 10% of the population in low-income countries have received at least one dose of the vaccine. This happened while more than nine billion doses of the vaccines were administered globally, predominantly in rich countries. On the backdrop of these man-made factors, the evolution of highly mutated variants of the virus is causing more uncertainties than the pre-vaccine time. If the vaccine inequities and hesitancy are not properly addressed, we are likely to enter into the vicious cycle of inequitable vaccine distribution leading to low vaccination rates in most low-income countries where the majority of the world population resides. This will ultimately enhance sustained transmission of the virus, leading to evolution of new variants of concern. As the highly mutated variants are likely to infect both vaccinated and unvaccinated individuals, it will inevitably lead to major doubts in the effectiveness and acceptance of the vaccines. In this review, we present how this vicious cycle may prolong the pandemic and discuss the importance of concerted global action to tackle it.Keywords: COVID-19, SARS-CoV-2, variants of concern, vaccine hesitancy, vaccine scepticism, vaccine inequity